MANAGEMENT OF PRODUCTIVE WAQF IN ISLAMIC BOARDING SCHOOL FOUNDATION ADLANYAH TAMPUS UJUNG GADING LEMBAH MELINTANG DISTRICT - Doli Witro; Ike Yulisa; Ali Hamzah (Mahkamah : Jurnal Kajian Hukum Islam, 2020)
Management of waqf must be directed to the management of waqf effectively and efficiently. Waqf management is the process of making planning, organizing, leadership, and controlling various businesses from Nazhir, then using all of the organization’s resources to achieve goals. According to data obtained by the Adlaniyah Islamic Boarding School Foundation has a wealth of land, the land came from the waqf of Nazri Adlani and was bought from residents. On that land, a class building and a dormitory have been partially planted with oil palm. The results of the oil palm plantations were initially used for school operations but in recent years the results of the oil palm plantations were taken by the foundation. While according to the provisions of waqf should be for the benefit of the people but in reality, it is used for personal gain. Departing from this, this writer conducted further research on the management of productive waqf at the Adlaniyah Islamic Boarding School Foundation Tampus Ujung Gading, Lembah Melintang District. In this study, the author uses the type of field research that is conducting field research by conducting direct interviews with administrators of the Adlaniyah Islamic Boarding School Foundation regarding the management of productive waqf at the Adlaniyah Islamic Boarding School Foundation Tampus Ujung Gading, Lembah Melintang District to find complete data related to this problem. In this study, the authors sought and collected data through interviews and documentation at the Adlaniyah Foundation Board and Islamic Boarding School Administrators. To obtain relevant data, the authors used data collection techniques, interviews, observations, and literature. After the data is collected, it will be analyzed by descriptive qualitative analysis methods. The results showed the Foundation in recent years did not provide direct subsidies every month for the benefit of the Islamic Boarding School due to some of the reasons above, although the foundation continued to assist incidentally to the Adlaniyah Islamic Boarding School.